Original tumour suppressor gene polycystic kidney and hepatic disease 1-like 1 is associated with thyroid cancer cell progression - Zheng, Chen (Oncol Lett, 2019)
In recent decades, thyroid cancer (TC) has become one of the most common endocrine malignancies. Next-generation sequencing of paired TC and adjacent healthy thyroid tissues demonstrated that polycystic kidney and hepatic disease 1-like 1 (PKHD1L1) may serve as a tumour suppressor gene in thyroid cancer. However, the function of PKHD1L1 in thyroid cancer is still unknown. To validate the results of whole-transcriptome resequencing, the expression levels of PKHD1L1 were evaluated in 58 pairs of papillary thyroid cancer (PTC) tissue samples and three thyroid cancer cell lines. In addition, The Cancer Genome Atlas (TCGA) data were used to analyse the relationship between PKHD1L1 and patient clinicopathological features. Cell Counting Kit-8, colony formation, migration and invasion assays were performed to assess the effects of PKHD1L1 knockdown in three TC cell lines. PKHD1L1 expression was significantly lower in thyroid carcinoma compared with that in matched normal tissue, and this result was consistent with that in TCGA cohort. TCGA data demonstrated that PKHD1L1 downregulation was associated with a number of aggressive clinicopathological features, such as histological type, lymph node metastasis (LNM), distant metastasis, tumour size and clinical stage. Logistic regression analysis of data from patients with PTC revealed that PKHD1L1 expression, histological type, age and tumour size were independent high-risk factors for LNM. The PKHD1L1 biological function was investigated in the three TC cell lines: TPC-1, KTC1 and BCPAP. A loss of function experiment demonstrated that PKHD1L1 knockdown promoted cell proliferation, colony formation and cell invasion in TC cell lines. In conclusion, PKHD1L1 may be a tumour suppressor gene associated with PC, and may be a potential therapeutic target in the future.